Superdough Inventory Web-based System - Kamalruzaman, Nik NurHani Nadirah; Omar, Nurul Aswa (Applied Information Technology And Computer Science, 2023)
Inventory is a very extensive asset for the company since it is one of the main sources of revenue generation and subsequent earnings for the company's shareholders represented by the turnover of inventory. However, Superdough Bakery's records their stock manually for daily, weekly, and monthly in a logbook which this can lead to a high probability to record stocks and quantities incorrectly. Moreover, they need to manually check which materials are low in stock since the logbook only displays a list of materials and it does not provide a notification to the admin and staff. Therefore, Superdough Inventory System is proposed to overcome the problem by helping the owner and staff of the bakery to record the stock systematically through low stock material and expense reports. It can also help in managing supplier details. This system is designed based on an object-oriented approach and waterfall methodology which contains seven modules.